Assessing the compliance of systematic review articles published in leading dermatology journals with the PRISMA statement guidelines: A systematic review protocol - Gundogan, Buket (Int J Surg Protoc, 2018)
INTRODUCTION: Systematic reviews and meta-analyses are methodologically rigorous studies that are said to form the reference standard for summarising evidence to guide health care. Reporting quality of reviews is of critical importance in order to judge the quality and risk of bias in a review to ensure sound healthcare decisions are made. This is particularly important in the field of dermatology due to the growing number of systematic reviews and their key role in informing healthcare decision within dermatology. A contemporary and comprehensive review of the compliance of dermatology systematic reviews and meta-analyses with the PRISMA checklist, in the highest impact factor dermatology journals, has not yet been assessed. To our knowledge, our review represents the most extensive study assessing reporting quality of systematic reviews and meta-analyses published within dermatology to date. METHODS AND ANALYSIS: Our protocol is reported in line with the Preferred reporting items for systematic review and meta-analysis protocols (PRISMA-P) 2015 guidelines. MEDLINE will be searched to look for systematic reviews and meta-analysis in selected years within the top four highest impact factor dermatology journals in 2017. Records and full texts will be screened independently by five researchers. Data will be extracted onto a standard data extraction database. A training session will take place to ensure accurate data extraction and scoring of studies with the PRISMA checklist. The data will be analysed and outcomes will be determined. Primary outcome will be the compliance of reviews with the PRISMA checklist.